Shaping the future of banana production in Asia: Challenges, trends, and strategic priorities to 2050 - Petsakos, Athanasios; Andrade, Robert; Carpentier, Sebastien; Blomme, Guy; Schiek, Benjamin; Gotor, Elisabetta (2025)
This brief provides a comprehensive overview of banana production and yield trends across Asia to 2050, drawing on expert insights to examine technological, environmental, and policy factors affecting yield variations. It identifies emerging challenges and opportunities in the banana sector to inform evidence-based policymaking, guide strategic investments, and support donors in enhancing regional food security and sustainable growth.